2012
DOI: 10.1111/j.1462-2920.2012.02827.x
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of hadopelagic microbial assemblages thriving at the deepest part of Mediterranean Sea, Matapan‐Vavilov Deep

Abstract: Summary The marine pelagic zone situated > 200 m below the sea level (bls) is the largest marine subsystem, comprising more than two‐thirds of the oceanic volume. At the same time, it is one of the least explored ecosystems on Earth. Few large‐scale environmental genomics studies have been undertaken to examine the phylogenetic diversity and functional gene repertoire of planktonic microbes present in mesopelagic and bathypelagic environments. Here, we present the description of the deep‐sea microbial communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
77
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 79 publications
9
77
0
1
Order By: Relevance
“…Figure S5). The Sea of Marmara (MARM) dataset showed similar distributions between subclade Ia (predominantly HTCC1062 type) and Ic (Supplementary Figure S6), and although the Matapan-Vavilov Deep (MATA) dataset had very little recruitment to any SAR11 genome (Supplementary Figure S7), consistent with the previous analysis (Smedile et al, 2013), those sequences that did recruit to SAR11 genomes were predominantly Ic-like. Longer Sanger shotgunsequencing reads from 4000 m at Station ALOHA (Konstantinidis et al, 2009) also demonstrated increased recruitment to the SAGs relative to other genomes in deeper water (Supplementary Figure S8).…”
Section: Comparative Genomicssupporting
confidence: 75%
See 1 more Smart Citation
“…Figure S5). The Sea of Marmara (MARM) dataset showed similar distributions between subclade Ia (predominantly HTCC1062 type) and Ic (Supplementary Figure S6), and although the Matapan-Vavilov Deep (MATA) dataset had very little recruitment to any SAR11 genome (Supplementary Figure S7), consistent with the previous analysis (Smedile et al, 2013), those sequences that did recruit to SAR11 genomes were predominantly Ic-like. Longer Sanger shotgunsequencing reads from 4000 m at Station ALOHA (Konstantinidis et al, 2009) also demonstrated increased recruitment to the SAGs relative to other genomes in deeper water (Supplementary Figure S8).…”
Section: Comparative Genomicssupporting
confidence: 75%
“…Metagenomes from ALOHA were previously described in Shi et al (2011). Data were also analyzed from 454 metagenomic sequences collected from Eastern Tropical South Pacific Oxygen Minimum Zone (Stewart et al, 2012), the Puerto Rico Trench (Eloe et al, 2011a), the Sea of Marmara (Quaiser et al, 2010) and the Matapan-Vavilov Deep in the Mediterranean Sea (Smedile et al, 2013). All raw data were trimmed of low-quality end sequences using Lucy (Chou and Holmes, 2001) and de-replicated using CDHIT-454 (Fu et al, 2012).…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…To compare the results among the different data sets, the number of reads was normalized considering the size of the contig and of the collection (number of reads per kilobase per gigabase of the collection). The meso and bathypelagic metagenome collections screened were: Marmara Sea-1000 m (Quaiser et al, 2011), Matapan-Vavilov Deep in the Mediterranean Sea-4900 m (Smedile et al, 2012), North Pacific subtropical gyre-ALOHA station-4000 m (Konstantinidis et al, 2009), Guaymas Basin hydrothermal vent in the Gulf of California (Lesniewski et al, 2012) and a metagenome obtained at 800 m in the South Atlantic Gyre (Swan et al, 2014).…”
Section: Metagenomic Recruitmentmentioning
confidence: 99%
“…Yet, current knowledge of the pelagic microbial community structure of the dark ocean, the largest biome in the biosphere, is based on a pool of samples collected at specific locations (DeLong et al, 2006;Martín-Cuadrado et al, 2007;Brown et al, 2009;Galand et al, 2010;Agogué et al, 2011;Eloe et al, 2011;Quaiser et al, 2011;Smedile et al, 2012;Wang et al, 2013;Wilkins et al, 2013;Ganesh et al, 2014) (Supplementary Figure S1) and thus are dwarf in comparison with the analyses of upper ocean microbial communities, which have indeed been assessed at global scales Yooseph et al, 2007;Zinger et al, 2011;Sunagawa et al, 2015). Whereas the deep ocean is often considered to be a rather uniform environment, the connectivity of pelagic microbial communities may be reduced by the limited mixing between water masses (Agogué et al, 2011;Hamdan et al, 2013) or modulated by advection (Wilkins et al, 2013) imposing limitations on the dispersion of marine microbes in this low-turbulence environment.…”
Section: Introductionmentioning
confidence: 99%